You ask (Journal of Parents and Teachers, 2025)
The article refers to a central question regarding how to make the most of vacations from an educational perspective. The author responds with 10 keys to achieving this goal, including: coexistence, nature, rest, fun, adventures, friendship, travel, reading, recovery, and acknowledging the paradox that real life is not about being on vacation continuously.
Keywords: vacations; keys; make the most of; education